Affective Learning and Psychophysiological Reactivity in Dementia Patients. (12th March 2012) - Blessing, Andreas; Keil, Andreas; Gruss, L. Forest; Zöllig, Jacqueline; Dammann, Gerhard; Martin, Mike
Abstract : We examined the association of faces with biographical information that varied in emotional content in patients with Alzheimer's disease and a healthy control group. During two experimental sessions, participants rated neutral male faces on dimensions of hedonic valence and emotional arousal, later paired with fictitious biographical information. Both groups changed their ratings of the faces according to the biographical content. Free recall and recognition were tested in the second session. Patients neither recalled the biographical information nor recognized the faces, whereas the controls did. In addition, psychophysiological measures were taken in response to the face stimuli. Patients showed significant heart rate modulation as a function of their emotion ratings, whereas the controls did not. No correlation of rating changes with skin conductance was found in any group. Results suggest that psychophysiological reactions such as heart rate changes may indicate preserved affective associative learning in dementia patients despite impaired explicit memory.